Effects of Axial Ligands on the Redox Properties of Manganese(III) meso-tetrakis(p-Hydroxyphenyl) Porphyrin - Thandiayyakone, V.; Murugan, A.; Ravikumar, C.R.; Rajkumar, T.; Kulandaisamy, A.; Muzaddadi, Ijaz Ullah; Manohar, A.; Arasu, P. Thillai; Chakrabarty, Mithun (Asian Journal of Chemistry, 2023)
In this work, meso-tetrakis(p-Hydroxyphenyl) porphyrin [T(p-OH)PP] and manganese(III) meso-tetrakis(p-hydroxyphenyl) porphyrin Mn[T(p-OH)PP] were synthesized and characterized. The UV-visible and cyclic voltammetry were used to evaluate the axial ligand and redox behaviour of Mn[T(p-OH)PP]. The addition of ethylamine, diethylamine and tertiary amines to Mn(III) meso-porphyrins distinguishes their axial ligand characteristics. The presence of ethylamine causes the octahedral geometry to transform into a square pyramidal structure. Cyclic voltammetry shows that Mn(III) converts to Mn(II) porphyrins. Additionally, the UV-visible spectrophotometry and cyclic voltammetry were also used to investigate the oxidation process.